(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article describes the introduction of media technology in professional education institutions, its importance today, its role in mastering theoretical and practical lessons. At the same time, topical issues such as students’ love for the Motherland, national values, ethical issues and the formation of security skills in the use of the media are highlighted.